2023
DOI: 10.1161/atvbaha.122.318573
|View full text |Cite
|
Sign up to set email alerts
|

Capacity for LDL (Low-Density Lipoprotein) Retention Predicts the Course of Atherogenesis in the Murine Aortic Arch

Abstract: BACKGROUND: To cause atherosclerosis, LDLs (low-density lipoproteins) must first pass through the endothelium and then become retained in the arterial matrix. Which of these two processes is rate-limiting and predicts the topography of plaque formation remains controversial. To investigate this issue, we performed high-resolution mapping of LDL entry and retention in murine aortic arches before and during atherosclerosis development. METHODS: Maps of LD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…Arrows are color coded to indicate crucial mechanisms in the retention and early modification of cholesterol-rich apoB lipoproteins within the arterial wall (yellow) and then strikingly maladaptive local responses to the retained and modified material that lead to plaque growth and progression (red). Lewis et al 8 focused on early LDL entry and retention, as well as early recruitment of macrophages. B , Summary of the findings by Lewis et al in the central zone of the inner curvature region of the proximal murine aorta after 3.5 weeks of hypercholesterolemia, with speculations about the physical state of the LDL retained there.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…Arrows are color coded to indicate crucial mechanisms in the retention and early modification of cholesterol-rich apoB lipoproteins within the arterial wall (yellow) and then strikingly maladaptive local responses to the retained and modified material that lead to plaque growth and progression (red). Lewis et al 8 focused on early LDL entry and retention, as well as early recruitment of macrophages. B , Summary of the findings by Lewis et al in the central zone of the inner curvature region of the proximal murine aorta after 3.5 weeks of hypercholesterolemia, with speculations about the physical state of the LDL retained there.…”
mentioning
confidence: 99%
“…The initial goal of Lewis et al was to resolve a conflict in the literature between LDL entry 9 versus LDL retention 1,10–12 as the rate-limiting step in early atherogenesis. While pursuing these studies, Lewis et al 8 made an unexpected finding: a zone within the inner (lesser) curvature region of the proximal murine aorta with unusual properties during early atherogenesis. The authors found that 3.5 weeks of hypercholesterolemia decreased 18-hour retention of labeled LDL in the inner curvature region of the proximal aortic arch.…”
mentioning
confidence: 99%
See 3 more Smart Citations